Microbial Degradation of a Recalcitrant Pesticide: Chlordecone - Chaussonnerie, Sébastien; Saaidi, Pierre-Loïc; Ugarte, Edgardo; Barbance, Agnès; Fossey, Aurélie; Barbe, Valérie; Gyapay, Gabor; Brüls, Thomas; Chevallier, Marion; Couturat, Loïc; Fouteau, Stéphanie; Muselet, Delphine; et al. (Frontiers in Microbiology, 2016)
Chlordecone (Kepone®) is a synthetic organochlorine insecticide (C10Cl10O) used worldwide mostly during the 1970s and 1980s. Its intensive application in the French West Indies to control the banana black weevil Cosmopolites sordidus led to a massive environmental pollution. Persistence of chlordecone in soils and water for numerous decades even centuries causes global public health and socio-economic concerns. In order to investigate the biodegradability of chlordecone, microbial enrichment cultures from soils contaminated by chlordecone or other organochlorines and from sludge of a wastewater treatment plant have been conducted. Different experimental procedures including original microcosms were carried out anaerobically over long periods of time. GC-MS monitoring resulted in the detection of chlorinated derivatives in several cultures, consistent with chlordecone biotransformation. More interestingly, disappearance of chlordecone (50 µg/mL) in two bacterial consortia was concomitant with the accumulation of a major metabolite of formula C9Cl5H3 (named B1) as well as two minor metabolites C10Cl9HO (named A1) and C9Cl4H4 (named B3). Finally, we report the isolation and the complete genomic sequences of two new Citrobacter isolates, closely related to Citrobacter amalonaticus, and that were capable of reproducing chlordecone transformation. Further characterization of these Citrobacter strains should yield deeper insights into the mechanisms involved in this transformation process.